Digital maturity and readiness model for multiple-case of Kazakhstan large companies - Almasbekkyzy, Aidana; Abdikerim, Daulet; Nabi, Daulet; Abdallah, Yasser Omar; Shehab, Essam (IEEE, 2021)
With the evolving of Industry 4.0 in the 21st century, digitalization gains popularity in companies, because it is a need that makes the company competitive and optimizes the work. Many factors influence the company and its transformation, especially in large companies, for example, financial situation, organizational culture, employees and their skills and talents, technology, and strategy. Based on these factors, models are developed to assess the digital readiness and maturity of the company. As a result of a comprehensive review of different models and current situations in large Kazakhstani companies, the model was developed and described together with the results of the model which was applied in different companies.
Keywords: digital readiness; digital maturity; digitalization; Industry 4.0